The effect of Tabata-style functional high-intensity interval training on cardiometabolic health and physical activity in female university students - Lu, Yining; Wiltshire, Huw D.; Baker, Julien Steven; Wang, Qiaojun; Ying, Shanshan (Frontiers in Physiology, 2023)
Introduction: The increasing prevalence of metabolic syndrome and physical inactivity enhances exposure to cardiometabolic risk factors in university students. High-intensity interval training (HIIT) improved cardiometabolic health in clinical adults but the evidence in the university setting is limited. Furthermore, few studies examined the effect of low-volume HIIT on habitual physical activity (PA). Therefore, the primary aim of this study was to evaluate the efficacy of 12-week Tabata-style functional HIIT for improving multiple cardiometabolic health outcomes and habitual PA. We also investigated whether changes in habitual PA over the intervention period had an impact on exercise-induced health outcomes. Methods: 122 female freshmen were randomized into the Tabata group (n = 60) and the control (n = 62). The Tabata training protocol involved 8 × 20 s maximal repeated functional exercises followed by 10 s rest with a frequency of 3 times per week for 12 weeks. Body composition, maximal oxygen uptake (VO2max), blood pressure (BP), blood lipids, fasting glucose and insulin, C-reactive protein and PA were objectively measured using standardized methods. Dietary intake was measured using a valid food frequency questionnaire. All variables were measured pre- and post-intervention. Results: Mixed linear modelling results showed that there were large intervention effects on VO2max (p < 0.001, d = 2.53, 95% CI: 2.03 to 3.00 for relative VO2max; p < 0.001, d = 2.24, 95% CI: 1.76 to 2.68 for absolute VO2max), resting heart rate (p < 0.001, d = −1.82, 95% CI: −2.23 to −1.37), systolic BP (p < 0.001, d = −1.24, 95% CI: −1.63 to −0.84), moderate-to-vigorous intensity physical activity (MVPA) (p < 0.001, d = 2.31, 95% CI: 1.83 to 2.77), total PA (p < 0.001, d = 1.98, 95% CI: 1.53 to 2.41); moderate effects on %BF (p < 0.001, d = -1.15, 95% CI: −1.53 to −0.75), FM (p < 0.001, d = −1.08, 95% CI: −1.46 to −0.69), high-density lipoprotein (HDL) (p < 0.001, d = 1.04, 95% CI: 0.65 to 1.42), total cholesterol (p = 0.001, d = −0.64, 95% CI: −1.00 to −0.26); small effects on BMI (p = 0.011, d = −0.48, 95% CI: −0.84 to 0.11), WC (p = 0.043, d = −0.37, 95% CI: −0.74 to −0.01), low-density lipoprotein (p = 0.003, d = −0.57, 95% CI: −0.93 to −0.19), HOMA-IR (p = 0.026, d = −0.42, 95% CI: −0.78 to −0.05) and fasting insulin (p = 0.035, d = −0.40, 95% CI: −0.76 to −0.03). Regression analysis showed that only the percentage change of HDL was associated with the change of MVPA (b = 0.326, p = 0.015) and TPA (b = 0.480, p = 0.001). Conclusion: From the findings of the study we can conclude that 12-week low-volume Tabata-style functional HIIT was highly effective for university female students to improve cardiorespiratory fitness, body fat, some cardiometabolic health outcomes and habitual PA.